2015
DOI: 10.14444/2020
|View full text |Cite
|
Sign up to set email alerts
|

Spinous Process splitting Laminectomy: Clinical outcome and Radiological analysis of extent of decompression

Abstract: IntroductionSpinous process splitting laminectomy (SPSL) is a useful technique in achieving adequate decompression for lumbar canal stenosis, has the advantage of simultaneously decompressing multiple levels and minimising injury to the paraspinal muscles. Some concern has been expressed over the efficacy of this technique in decompressing lateral recesses. This study was undertaken to assess the clinical outcome of SPSL technique and radiologically assess the extent of decompression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 25 publications
(50 reference statements)
1
10
0
Order By: Relevance
“…12 Facet-preserving decompression has the benefit of offering a less morbid alternative for patients with primarily leg symptoms and stenosis associated with spondylolisthesis or scoliosis. 8,12,14 Our study confirms that endoscopic decompression causes very little destruction to both the ipsilateral and contralateral facets. We do not have a comparison group to draw any conclusions about the benefit of this procedure over an open or tubular laminectomy in facet preservation.…”
Section: Discussionsupporting
confidence: 72%
“…12 Facet-preserving decompression has the benefit of offering a less morbid alternative for patients with primarily leg symptoms and stenosis associated with spondylolisthesis or scoliosis. 8,12,14 Our study confirms that endoscopic decompression causes very little destruction to both the ipsilateral and contralateral facets. We do not have a comparison group to draw any conclusions about the benefit of this procedure over an open or tubular laminectomy in facet preservation.…”
Section: Discussionsupporting
confidence: 72%
“…Our sample included patients who were unresponsive to non-operative conservative treatment for at least 12 weeks and who showed progressive symptoms despite continued non-operative treatment. The exclusion criteria included patients with marked neuroforaminal stenosis (treated by fusion or foraminal decompression at our institution, described elsewhere) [ 11 ], over three levels of stenosis (treated by spinous process splitting laminectomy at our institution, described elsewhere) [ 12 ], any prior spine surgery at any operative level in consideration of morphological changes, any prior lumbar fusion at any level to avoid adjacent disc disease, or requiring additional concurrent treatments. Patients with segmental instability, lytic spondylolisthesis, and degenerative spondylolisthesis over grade 2, with predominant lower-back pain were also excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…A study conducted by Zhang et al 19 reported that the mean canal stenosis index after posterior indirect reduction and pedicle screw fixation without laminectomy was 84.8% ( sd 7.3%) compared with 32.9% ( sd 7.8%) before the operation, which indicated that there is a more than twofold increase of the mean canal stenosis index following the procedure. Other studies conducted by Lee et al 20 reported that the ratio increase of cross-sectional spinal canal area was 163.8%. According to the study conducted by Mlyavykh et al, 8 lengthening of less than 5 mm with pedicle-lengthening osteotomy could provide favourable clinical results and increase spinal canal volume by 65.2%.…”
Section: Discussionmentioning
confidence: 84%